PENGARUH ORGANIZATIONAL COMMITMENT DAN PROFESSIONAL COMMITMENT TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR KARYAWAN PT. TELKOMSEL PEKANBARU - Putra Gema Azan; Dewita Suryatiningsih; Nuryanti ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The research was conducted at PT. Telkomsel Pekanbaru, with the aim to analyze the influence of Organizational Commitment and Professional Commitment on Organizational Citizenship Behavior to employees. The population in this research were 134 people , by using the obtained sample slovin numbered 100 people. Furthermore, the data were analyzed using multiple linear regression analysis of the data by using SPSS 21. The results showed that the variable Organizational Commitment and Professional Commitment simultaneously significant effect on the Organizational Citizenship Behavior . Furthermore, based on the partial test can be seen that Organizational Commitment and Professional Commitment significantly effect on Organizational Citizenship Behavior employee. To the company expected need to increase the commitment of its employees in terms of a sense of responsibility towards the wider community and the dangers to the organization. Likewise with Professional Commitment, Expected to employees in order to more closely follow developments in the company. In addition, leaders must also provide motivation to work so that Organizational Citizenship Behavior can be improved.Keywords :Organizational Commitment, Professional and Citizenship Behavior